Measurement of public health benefits of physical activity: validity and reliability study of the international physical activity questionnaire in Hungary - Ács, Pongrác (BMC Public Health, 2020)
BACKGROUND: To ensure accurate measurement of the health benefits of habitual physical activity in large sample epidemiological studies, physical activity questionnaires (PAQs) are the most feasible methods. Therefore, the purpose of this study was the validation and cultural adaptation to the Hungarian population of the International Physical Activity Questionnaire (IPAQ-HL). METHODS: A cross-sectional study among Hungarian healthy adults (age 21.375 ± 1.940 years, n = 120) was performed comparing measures of last 7 days IPAQ-HL self- administered questionnaire and obtained accelerometer (Actigraph GT3X) data for concurrent validity, reassessed by a random subsample (n = 33) to measure reliability. RESULTS: Our results indicate acceptable criterion validity for total physical activity, moderate to vigorous physical activity (R = 0.387, p < 0.001; R = 0.331 p < 0.001 respectively) and moderate physical activity (R = 0.193, p = 0.034). The ICC scores revealed moderate to good correlations (ICC = 0.744–0.942, p < 0.001). Moderate Kaiser–Meyer–Olkin measure (0.531, p < 0.001) and good reproducibility for vigorous, moderate to vigorous and moderate activities was found for IPAQ-HL in the studied population. Nevertheless, like analogous self-reports in other languages, it overestimates the time spent on physical activity. CONCLUSIONS: IPAQ-HL proved to be a reasonably valid measure for population prevalence epidemiological studies and is suggested for use to develop public health policy recommendations or to optimize public health interventions. However, the results on vigorous activity should be interpreted with caution, the questionnaire showed moderate validity for this particular intensity.